Vat photopolymerisation 3D printing of silicon carbide ceramics utilizing NIR light - Soon, Chia Wen (Nanyang Technological University, 2023)
Vat photopolymerisation is an additive manufacturing technique that allows the freeform fabrication of various structures with complex geometries, expanding 3D printing in a plethora of applications. However, the vat photopolymerisation of silicon carbide (SiC) has been largely limited, due to its high UV light absorbance and refractive index. Thus far, approaches in improving the cure depth have been limited to particle modification or lowering the volume fraction of SiC powders. Yet, obtaining dense SiC ceramics has been inhibited via these approaches. In this work, we explore an alternative method to 3D print SiC ceramics via vat photopolymerisation with near-infrared (NIR) light. A detailed investigation into materials for NIR photopolymerisation was carried out, and a suitable NIR photosystem was established. The penetration depth of NIR light in SiC ceramic slurries was probed and compared with that of UV light. Higher cure depths of up to 40.8 ± 2.3 μm were obtained when using NIR light as compared to UV light (30.0 ± 3.3 μm). Higher spatial resolutions and fidelities were also obtained with the utilisation of NIR light for photopolymerisation. As a proof-of-concept, a commercially available liquid crystal display (LCD) printer was modified to demonstrate NIR-based printing of SiC structures. The preliminary findings from this work paves the way for exploring alternative light sources for the vat photopolymerisation of carbide-based ceramics.